2012
DOI: 10.1002/prca.201200044
|View full text |Cite
|
Sign up to set email alerts
|

Proteome‐base biomarkers in diabetes mellitus: Progress on biofluids' protein profiling using mass spectrometry

Abstract: The worldwide number of individuals suffering from diabetes mellitus (DM) has been projected to rise from 171 million in 2000 to 366 million in 2030. Identification of specific biomarkers for prediction and monitoring of DM is needed not only for the adequate screening diagnosis but also to assist the design of interventions to prevent or delay progression of this pathology and its attendant complications. Proteomic methods based on MS hold special promise for the identification of novel biomarkers that might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 123 publications
(254 reference statements)
1
4
0
Order By: Relevance
“…Changes in the abundance of these proteins were analysed in relation to BMI and 64 unique proteins were successfully identified by MS/MS. The identified proteins were classified according to their biological process showing a similar distribution to those biomarkers previously reported for serum and other biofluids from diabetic patients45, except for metabolic processes, which are over-represented in the present study. When comparing the 64 proteins identified with the HDPP lists, it is important to mention that 37 proteins already reported in European population were detected in Mexican patients, which shows a validation of our study but also that those proteins do not have any relation with ethnicity.…”
Section: Discussionsupporting
confidence: 72%
“…Changes in the abundance of these proteins were analysed in relation to BMI and 64 unique proteins were successfully identified by MS/MS. The identified proteins were classified according to their biological process showing a similar distribution to those biomarkers previously reported for serum and other biofluids from diabetic patients45, except for metabolic processes, which are over-represented in the present study. When comparing the 64 proteins identified with the HDPP lists, it is important to mention that 37 proteins already reported in European population were detected in Mexican patients, which shows a validation of our study but also that those proteins do not have any relation with ethnicity.…”
Section: Discussionsupporting
confidence: 72%
“…Proteomic analysis has been widely used to identify biomarkers for the diagnosis and treatment response of various diseases [5]. Previous studies using proteomic analysis have identified several proteins that are possible novel biomarkers related to the development of metabolic problems, such as obesity, diabetes and elevated lipids, in the general population [6][8].…”
Section: Introductionmentioning
confidence: 99%
“…Combining molecular signatures with demographic information and other donor and recipient factors, obtained from linkage to a transplant registry, will further increase the power of such profiles to predict outcomes. The establishment of a bio-bank facilitates this type of research, which has been successful in other specialities including cardiac research and diabetes [ 17 ]. The complexity of biomarker research and the correlation with individual markers and signatures of injury and how they correlate with clinically relevant outcomes is recognised.…”
Section: The Role Of Bio Banks In Organ Donationmentioning
confidence: 99%